2021
DOI: 10.1111/1365-2745.13801
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient enrichment increases invertebrate herbivory and pathogen damage in grasslands

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 80 publications
6
41
1
Order By: Relevance
“…These 24 plots were randomly assigned to 0, 5, 10, or 15 g/m 2 nitrogen treatments, supplied as ammonium nitrate (applied every mid‐June from 2011 to 2021), with six replicates for each treatment (see Liu et al, 2017 for a full description). Our previous studies have confirmed that nitrogen addition significantly decreased plant species richness (Liu et al, 2016), shifted mean plant functional traits, and increased community‐level foliar fungal disease prevalence by both direct (supporting the “nitrogen‐disease hypothesis”; Dordas, 2008; Ebeling et al, 2022; Veresoglou et al, 2013) and indirect effects (i.e., shifts in plant community composition toward species with competitive growth but high disease susceptibility) (Liu et al, 2017).…”
Section: Methodssupporting
confidence: 64%
“…These 24 plots were randomly assigned to 0, 5, 10, or 15 g/m 2 nitrogen treatments, supplied as ammonium nitrate (applied every mid‐June from 2011 to 2021), with six replicates for each treatment (see Liu et al, 2017 for a full description). Our previous studies have confirmed that nitrogen addition significantly decreased plant species richness (Liu et al, 2016), shifted mean plant functional traits, and increased community‐level foliar fungal disease prevalence by both direct (supporting the “nitrogen‐disease hypothesis”; Dordas, 2008; Ebeling et al, 2022; Veresoglou et al, 2013) and indirect effects (i.e., shifts in plant community composition toward species with competitive growth but high disease susceptibility) (Liu et al, 2017).…”
Section: Methodssupporting
confidence: 64%
“…Across grassland soils, N addition can alter tissue stoichiometry, resulting in more nutrient‐rich tissues that are more attractive to herbivores (Anderson et al, 2018; Firn et al, 2019; Hillebrand et al, 2009; Mattson, 1980). Specifically, insect, pathogen, and fungal damage on leaves can increase at high levels of N addition in grasslands (Ebeling et al, 2021; Lind et al, 2017; Throop & Lerdau, 2004); high rates of pathogen damage with N addition have previously been found in the highest N addition plots of this experiment (Ebeling et al, 2021). Additionally, Seabloom et al (2017) found that, across a spectrum of plant diversity, pathogens and fungi removed a constant proportion of plant biomass.…”
Section: Discussionmentioning
confidence: 59%
“…The work presented here points to many interesting avenues for further development and investigation. For example, we expect that herbivory reduced biomass in NPK plots, as nutrient addition attracts grazing (Borer et al, 2020; Borer, Seabloom, et al, 2014; Ebeling et al, 2021; Hodapp et al, 2018), possibly explaining some site‐level variation. How these relationships change with grazing exclusion is currently an open question.…”
Section: Discussionmentioning
confidence: 99%